HISTORY MANAGEMENT OF DATA – SLOWLY CHANGING DIMENSIONS - Wancerz, Marek; Wancerz, Paweł (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The article describes few methods of managing data history in databases and data marts. There are many types of dealing with the history of the data. This article will show us some examples, point advantages and disadvantages of each of the method and show us possible scenarios of use.